Institutional change and political continuity in post-Soviet Central Asia : - Luong, Pauline Jones. (Cambridge University Press, 2002)
The establishment of electoral systems in Kazakhstan, Kyrgyzstan, and Uzbekistan presents a complex set of empirical puzzles as well as a theoretical challenge. Why did three states with similar cultural, historical, and structural legacies establish such different electoral systems? How did these distinct outcomes result from strikingly similar institutional design processes? Explaining these puzzles requires understanding not only the outcome of institutional design but also the intricacies of the process that led to this outcome. Moreover, the transitional context in which the three states designed new electoral rules necessitates an approach that explicitly links process and outcome in a dynamic setting. This book provides such an approach. It depicts institutional design as a transitional bargaining game in which the dynamic interaction between the structural-historical and immediate-strategic contexts directly shapes actors' perceptions of shifts in their relative power, and hence, their bargaining strategies. Thus, it both builds on the key insights of the dominant approaches to explaining institutional origin and change and transcends these approaches by moving beyond the structure versus agency debate.